Poly(Butylene Terephthalate) Based Composites Containing Alumina Whiskers: Influence of Filler Functionalization on Dielectric Properties - Pietro Russo; Francesca Cimino; Domenico Acierno; Giovanni Lupò; Carlo Petrarca (International Journal of Polymer Science)
Poly(butylene terephthalate) (PBT) is one of the most widely used semicrystalline thermoplastics polyester because of its superior thermal and mechanical properties, high dimensional stability and excellent processability. In this research PBT-based nanocomposites, including various amounts (up to 10 wt%) of commercial alumina whiskers, have been prepared by using a Brabender internal chamber mixer and analysed in terms of morphological features and dielectric properties. Specific attention has been focused on the effect of the filler functionalization considering 3-glycidoxy propylmethoxysilane (GPS) or 3-methacryloxypropyltrimethoxysilane (MPS) as coupling agents. Tests, performed on compounds filled with neat and functionalized alumina whiskers, show a clear dependence of relative dielectric permittivity εr, invariance of dissipation factor (tgδ), and a sensible increase of volume electrical resistivity (ρv) with the filler’s content and are encouraging for a future introduction of such composites in many electrical applications.